Genotyping of Hepatitis C Virus isolated from Libyan Patients by Line Immune Probe Assay - Elgadi, Suliman A. (International Journal of Pharmaceutical & Biological Archive, 2021)
Introduction: Hepatitis C virus (HCV) genotyping is important in the routine diagnosis and management of chronic hepatitis C infections. The reference method used for HCV genotype determination is direct sequencing of the NS5B or E1 regions of HCV genome by means of â€œin-houseâ€ techniques followed by sequence alignment with prototype sequences and phylogenetic analysis. Material and Method: Blood samples were collected from 75 HCV- infected Libyan patients (age range 8â€“70 years mean 24 years), out of them 32 of them females (43%) and 43 males (57%). Forty-three (57.3%) have confection with human immunodeficiency virus (HIV) infection. Result: Out of the 75 samples examined in this study, 45 (60%) were found to belonging HCV genotype 4 followed by 20 (26.7%) subtype 1a. Other subtypes 2a/2c, subtype 1b; subtype 1a/1b; and genotype 2 all represented 5.3%; 5.3%; 1.3%; and 1.3%, respectively. Conclusion: In conclusion, the distribution of HCV genotypes in Libya is consistent with other neighboring countries.